Experiences of children and their caregivers affected by multidrug-resistant tuberculosis in Cape Town, South Africa. - Abenathi Mcinziba; Dillon T Wademan; Klassina Zimri; Stephanie Jacobs; Khanyisa Mcimeli; H Simon Schaaf; Anneke C Hesseling; James A Seddon; Thomas Wilkinson; Graeme Hoddinott (PLoS ONE)
Background Approximately 30,000 children (<15 years) develop multidrug-resistant (MDR) tuberculosis (TB) each year. MDR-TB severely impacts the lives of children and their families, yet data exploring their experiences are limited. We describe the experiences of children routinely treated for MDR-TB and their caregivers throughout their MDR-TB journeys in Cape Town, South Africa. Methods We conducted a series of three in-depth qualitative interviews (48 interviews in total) with 17 children (<15 years) and/or their caregivers between April 2021 and September 2021. We selected children who had been routinely treated for MDR-TB between 2018 and 2021. We applied a deductive, thematic analysis to case summaries with illustrative examples from interviews. Findings Children had negative experiences throughout their MDR-TB journey, before their diagnosis, during the diagnostic process, through treatment, and beyond treatment completion. Children and their caregivers experienced delays in acquiring accurate and timely MDR-TB diagnosis; stating lack of symptom recognition and repeated referrals between health facilities. Once on treatment, caregivers experienced challenges administering MDR-TB medication as children resisted taking their medications due to poor palatability, tolerability, and negative side effects. Some caregivers reported that, beyond treatment, children experienced extended physical challenges such as shortness of breath. Additionally, MDR-TB diagnosis and treatment negatively affected family life, as caregivers adjusted household spending toward foods that facilitated ingestion and mitigated side effects. Caregivers also juggled between attending to their children's MDR-TB care and other household priorities. Conclusion There are multifactorial challenges experienced by children and their caregivers throughout their MDR-TB journey. Research is needed to develop holistic interventions for child-caregiver-centred psychosocial support to mitigate the negative impact of MDR-TB on children and their caregivers through prevention, earlier diagnosis, and simpler, child-friendly regimens. [1112,3].